2018
DOI: 10.3390/genes9090433
|View full text |Cite
|
Sign up to set email alerts
|

Specific LTR-Retrotransposons Show Copy Number Variations between Wild and Cultivated Sunflowers

Abstract: The relationship between variation of the repetitive component of the genome and domestication in plant species is not fully understood. In previous work, variations in the abundance and proximity to genes of long terminal repeats (LTR)-retrotransposons of sunflower (Helianthus annuus L.) were investigated by Illumina DNA sequencingtocompare cultivars and wild accessions. In this study, we annotated and characterized 22 specific retrotransposon families whose abundance varies between domesticated and wild geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…The sample for genome sequencing was collected from young leaf tissue (0.5-1 cm in diameter) obtained from a single female plant of the Italian F. carica cultivar Dottato. Genomic DNA was isolated using the CTAB method as modified by Mascagni et al (2017Mascagni et al ( , 2018. For gel electrophoresis we used a Lambda Eco/Hind marker to size the linear double-stranded DNA and isolate only fragments with a molecular weight greater than 20 000 bp.…”
Section: Dna Extraction and Genome Sequencingmentioning
confidence: 99%
“…The sample for genome sequencing was collected from young leaf tissue (0.5-1 cm in diameter) obtained from a single female plant of the Italian F. carica cultivar Dottato. Genomic DNA was isolated using the CTAB method as modified by Mascagni et al (2017Mascagni et al ( , 2018. For gel electrophoresis we used a Lambda Eco/Hind marker to size the linear double-stranded DNA and isolate only fragments with a molecular weight greater than 20 000 bp.…”
Section: Dna Extraction and Genome Sequencingmentioning
confidence: 99%
“…Genetic studies of sunflower domestication revealed that contrary to findings in other plant species, where it was found that the phenotypic differences caused by domestication are due to a smaller number of genes with a strong effect [ 14 , 15 ], in sunflower, there is a larger number of genes involved in domestication, with the majority of genes showing small or moderate phenotypic effect [ 6 , 8 ]. Another difference between wild and cultivated sunflowers is the copy number of long terminal repeats (LTR) retrotransposons and splicing divergence [ 16 ]. A detailed list of domestication related quantitative trait loci (QTL) mapped in different crosses between cultivated and wild sunflower and primitive and wild sunflower is given in Table A1 .…”
Section: Sunflower—history and Domesticationmentioning
confidence: 99%
“…For each CACTA sequence, the genomic abundance was first assessed by mapping DNA reads of the sunflower genome, downloaded from NCBI (SRR5004633), according to the strategy already used for repetitive sequences in Mascagni et al [41,42]. Illumina HiSeq 2000 reads were preprocessed to remove Illumina adapters, then quality-trimmed using the default settings, and the lengths of reads were defined at 90 nt.…”
Section: Abundance Estimation and Dna Mapping Proceduresmentioning
confidence: 99%